Multi‐parametric magnetic resonance imaging for radiation treatment planning. Issue 4 (3rd March 2022) - Omari, Eenas A.; Zhang, Ying; Ahunbay, Ergun; Paulson, Eric; Amjad, Asma; Chen, Xinfeng; Liang, Ying; Li, X. Allen
Abstract: In recent years, multi‐parametric magnetic resonance imaging (MpMRI) has played a major role in radiation therapy treatment planning. The superior soft tissue contrast, functional or physiological imaging capabilities, and the flexibility of site‐specific image sequence development has placed MpMRI at the forefront. In this article, the present status of MpMRI for external beam radiation therapy planning is reviewed. Common MpMRI sequences, preprocessing, and quality assurance strategies are briefly discussed, and various image registration techniques and strategies are addressed. Image segmentation methods including automatic segmentation and deep learning techniques for organs at risk and target delineation are reviewed. Due to the advancement in MRI‐guided online adaptive radiotherapy, treatment planning considerations addressing MRI only planning are also discussed.